HIV Stigma and Discrimination: Perspectives and Personal Experiences of Healthcare Providers in Yogyakarta and Belu, Indonesia - Fauk, Nelsensius Klau; Ward, Paul Russell; Hawke, Karen; Mwanri, Lillian (Frontiers in Medicine, 2021)
Stigma and discrimination are major challenges facing People Living with HIV/AIDS (PLWHA) globally due to their HIV status. As part of a larger qualitative study in Yogyakarta and Belu, Indonesia, using in-depth interviews with 92 PLWHA (52 women, 40 men) and 20 healthcare providers, this paper describes perspectives and personal experiences of the 20 healthcare providers, relating to HIV stigma and discrimination toward PLWHA in both study settings. The healthcare providers were recruited from healthcare facilities providing HIV-related healthcare services, using a snowball sampling technique. A qualitative framework analysis was used to guide data analysis. Health stigma and discrimination framework guided the conceptualisation and discussion of the findings. The findings presented the views and perspectives of healthcare providers that HIV stigma and discrimination toward PLWHA still occurred within families, communities and healthcare settings. These were reflected in negative labelling, separation of personal belongings, avoidance, denial of treatment and rejection of PLWHA by healthcare providers, family and community members. Some healthcare providers reported that they had personally stigmatised and discriminated against PLWHA. A lack of knowledge about HIV, fear of contracting HIV, personal values, religious thoughts and sociocultural values and norms, were reported as drivers or facilitators behind this HIV-related stigma and discrimination. The findings indicate the importance of continued HIV/AIDS education for families, community members and healthcare providers, to raise awareness and to ensure that healthy and professional support systems are in place for PLWHA. The findings indicate the need to enhance improvement within the healthcare or HIV care system to adequately address the needs of PLWHA, which may facilitate their early initiation of HIV treatment and better treatment adherence and retention to increase Cluster of Differentiation 4 (CD4) count and suppress viral load. Future studies are also needed to explore the role that government and non-government institutions can play in improving health service delivery for people newly diagnosed with HIV and those living with HIV/AIDS.